Potential of targeting signal-transducing adaptor protein-2 in cancer therapeutic applications - Taiga Maemoto; Yuto Sasaki; Fumiya Okuyama; Yuichi Kitai; Kenji Oritani; Tadashi Matsuda (Open Exploration Publishing Inc., 2024)
Adaptor proteins play essential roles in various intracellular signaling pathways. Signal-transducing adaptor protein-2 (STAP-2) is an adaptor protein that possesses pleckstrin homology (PH) and Src homology 2 (SH2) domains, as well as a YXXQ signal transducer and activator of transcription 3 (STAT3)-binding motif in its C-terminal region. STAP-2 is also a substrate of breast tumor kinase (BRK). STAP-2/BRK expression is deregulated in breast cancers and enhances STAT3-dependent cell proliferation. In prostate cancer cells, STAP-2 interacts with and stabilizes epidermal growth factor receptor (EGFR) after stimulation, resulting in the upregulation of EGFR signaling, which contributes to cancer-cell proliferation and tumor progression. Therefore, inhibition of the interaction between STAP-2 and BRK/EGFR may be a possible therapeutic strategy for these cancers. For this purpose, peptides that interfere with STAP-2/BRK/EGFR binding may have great potential. Indeed, the identified peptide inhibitor successfully suppressed the STAP-2/EGFR protein interaction, EGFR stabilization, and cancer-cell growth. Furthermore, the peptide inhibitor suppressed tumor formation in human prostate- and lung-cancer cell lines in a murine xenograft model. This review focuses on the inhibitory peptide as a promising candidate for the treatment of prostate and lung cancers.